Aspects of the modern biogens runoff formation in the central part of the Russian Plain - Dolgov Sergey; Koronkevich Nikolay; Barabanova Elena (E3S Web of Conferences, 2020)
The removal of biogenic substances (mineral nitrogen and phosphorus) from river catchments and its modern aspects of formation are considered. A rough estimate of the annual water-biogenic balance for the Linda and Kudma river catchments, which are the tributaries of the Cheboksary reservoir, and the river catchments of the Kursk region is presented. It is shown that the diffuse removal of biogens from river catchments exceeds their removal into water bodies with wastewater. Not only anthropogenic, but also natural factors play an important role in the biogens export to the rivers and waterbodies. Resent changes in biogens removal from catchments are assessed.